Simple Pretreatment and Portable UV‐Vis Spectrum Instrument for the Rapid Detection of Melamine in Milk Products. Issue 4 (7th July 2015) - Xie, Wanyi; Huang, Yu; Yun, Wen; Tang, Dongyun; Zhang, Hua; Du, Chunlei; Zhu, Yonghong; Zhang, Wei
Abstract In this paper, we report a simple and reliable method for detection of melamine (MEL) in the field of milk products safety screening. This method is developed based on gold nanoparticle (AuNP) probe as the presence of MEL can induce the AuNPs to aggregate and make its color change from wine red to purple. This color change can be quantitatively recorded by a portable UV‐vis spectrophotometer so as to calculate the amount of MEL simultaneously. Herein, alcohol is used as MEL extraction solvent without other complex sample processing method because alcohol can easily denature the casein in milk. Furthermore, under the optimized condition, only about 15 min for whole detection process is required to determine the amount of MEL in milk, and the detection limit of MEL can be as low as 2 ppm. Practical Applications At present, analysis of melamine (MEL) in these milk products is urgent and required. However, most of the published assays require expensive instruments and complicated pretreatment. Herein, a reliable and simple method for MEL detection for field screening of milk was developed, which is based on gold nanoparticle probe with a portable UV‐vis spectrophotometer. Herein, ethanol was used as an environmentally friendly solvent to extract MEL from milk, and the whole detection process only required about 15 min.